Lifetime psychopathology in child and adolescent offspring of parents diagnosed with schizophrenia or bipolar disorder: a 2-year follow-up study. - De la Serna, E.; Ilzarbe, D.; Sugranyes, G.; Baeza, I.; Moreno, D.; Rodríguez-Toscano, E.; Espliego, A.; Ayora, M.; Romero, S.; Sánchez-Gistau, V.; Castro-Fornieles, J. (European Child & Adolescent Psychiatry, 2021)
Having one parent diagnosed with a severe mental disorder is considered one of the main risk factors for developing that disorder in adulthood, and it also increases the risk of a wide range of mental disorders in the offspring. The aim of this study is to compare the prevalence of several psychopathological diagnoses, the presence of prodromal symptoms, and global functioning in offspring of parents with schizophrenia or bipolar disorder and in offspring of controls at baseline and 2-year follow-up. This study included 41 offspring of parents with schizophrenia, 90 offspring of parents with bipolar disorder, and 107 offspring of controls (mean age 11.7 ± 3.2 at baseline and 13.9 ± 3.2 at follow-up). The prevalence of psychopathology and comorbidity was higher in offspring of parents with schizophrenia and offspring of parents with bipolar disorder than in offspring of controls at baseline and at 2-year follow-up. Interestingly, mood disorders were more prevalent in offspring of parents with bipolar disorder and disruptive disorders were more prevalent in offspring of parents with schizophrenia. Prodromal symptoms were more frequent in offspring of parents with schizophrenia than in offspring of controls, while the offspring of parents with bipolar disorder showed an intermediate pattern. Finally, global functioning was lower in the offspring of parents with schizophrenia than the offspring of parents with bipolar disorder and the offspring of controls. Screening patients' children is clinically relevant, since, as a group, they have an elevated risk of developing a psychiatric disorder and of experiencing their first symptoms during childhood and adolescence.